Effect of time on the post-irradiation curing of six resin-based composites. Issue 8 (August 2020) - Kaiser, Christina; Price, Richard Bengt
Abstract: Objectives: To evaluate the effect of time on the Vickers microhardness (VH) at the top and bottom surfaces of six conventional resin-based composites (RBCs) up to twelve weeks after light curing. Methods: Five specimens of Filtek Supreme Ultra, Herculite Ultra, Mosaic Ultra, Tetric EvoCeram, TPH Spectra HV, and Venus Pearl were packed into opaque molds that were 2.3 mm in diameter and 2.5 mm deep. The uncured RBC specimens were covered by a polyester strip and photo-cured with an Elipar DeepCure-S light-curing unit (LCU) according to the manufacturer's instructions. After irradiation, the polyester strip was removed, and the Vickers microhardness was measured immediately at top and bottom surfaces. The hardness measurements were repeated after 30 min, 1 h, 2 h, 4 h, 24 h, 1 week, 4 weeks, and 12 weeks. In between, the specimens were stored in dry and dark conditions at 37 °C. Two-way ANOVA ( α  = 0.05) followed by Tukey–Kramer post hoc multiple comparison tests were used to determine where statistically significant differences existed. Results: The micro-hardness values at the top surface always exceeded those at the bottom surface. A significant logarithmic increase of the micro-hardness due to post-irradiation curing took place between 30 min and 24 h ( p  < 0.05). There was no significant increase in the VH after 24 h. Depending on the RBC, compared to the immediate values the hardness 24 h post-irradiation had increased by 11–27% at the top surface and by 21–58% at the bottom. Significance: Even after 12 weeks, the bottom hardness values never reached the top microhardness values. The results of studies that wait 24 h or longer before measuring the properties of RBC specimens will be significantly enhanced by the impact of post-irradiation curing. Especially within the first 4 h, the time when specimens are measured is critical information and should be reported.